2021
DOI: 10.1073/pnas.2025570118
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of neoantigen-specific T cells in cancer resistant to immune checkpoint therapies

Abstract: Neoantigen-specific T cells are strongly implicated as being critical for effective immune checkpoint blockade treatment (ICB) (e.g., anti–PD-1 and anti–CTLA-4) and are being targeted for vaccination-based therapies. However, ICB treatments show uneven responses between patients, and neoantigen vaccination efficiency has yet to be established. Here, we characterize neoantigen-specific CD8+ T cells in a tumor that is resistant to ICB and neoantigen vaccination. Leveraging the use of mass cytometry combined with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 80 publications
2
31
0
Order By: Relevance
“…An increased presence of exhausted T cells and augmented IFN responses suggest that MRTX treatment has the potential to sensitize these tumors to ICB. Nevertheless, in this immune-resistant model (28), addition of an anti-PD1 antibody (Fig. 7A) or a combination of anti-PD-L1 and anti-LAG-3 antibodies (fig.…”
Section: Kras G12c Inhibition Synergizes With Checkpoint Blockade Onl...mentioning
confidence: 89%
“…An increased presence of exhausted T cells and augmented IFN responses suggest that MRTX treatment has the potential to sensitize these tumors to ICB. Nevertheless, in this immune-resistant model (28), addition of an anti-PD1 antibody (Fig. 7A) or a combination of anti-PD-L1 and anti-LAG-3 antibodies (fig.…”
Section: Kras G12c Inhibition Synergizes With Checkpoint Blockade Onl...mentioning
confidence: 89%
“…An increased presence of exhausted T cells and augmented IFN responses suggest that MRTX treatment has the potential to sensitize these tumours to ICB. Nevertheless, in this immune-resistant model ( 28 ), addition of an anti-PD1 antibody (Fig 7A) or a combination of anti-PD-L1 and anti-LAG3 antibodies (Fig S6A) did not improve the response to KRAS G12C inhibition alone, nor did it enhance the TME remodeling driven by KRAS G12C inhibition (Fig 7B). We found that the lack of therapeutic response observed was not due to insufficient antigen presentation by the tumour cells, as re-expression of the epigenetically silenced H2Kb by treatment with the DNA methyltransferase inhibitor Decitabine in these cells did not improve responses to MRTX+PD1 (Fig S6B and S6C).…”
Section: Resultsmentioning
confidence: 91%
“…Consistent with this, a recent study reported that CD8 + TILs specific for mRiok1 (the same sequence as the immunogenic short peptide S50 in our study) were present in LLC1 tumors and were expanded after anti-PD-1 or anti-CTLA-4 treatment. Nonetheless, as in our model, a combination of prophylactic mRiok1 vaccination, anti-PD-1, and anti-CTLA-4 also failed to induce a protective anti-tumor response [ 26 ].…”
Section: Discussionmentioning
confidence: 98%